Research on the relationship between marital commitment, sacrifice behavior and marital quality of military couples - Lin, Lemin; Guo, Hang; Duan, Lisa; He, Li; Wu, Chaoliang; Lin, Zhangya; Sun, Jiangnan (Frontiers in Psychology, 2022)
Based on the actor-partner interdependence model, this paper studied the relationship between marital commitment, sacrifice behavior and marital quality of military couples. A convenience sample of 171 Chinese military couples from Guangdong, Jiangsu and Sichuan province was used. All participants completed the self-report questionnaires independently including the Dimension of Commitment Inventory (DCI), the Couples Sacrifice Behavior Scale (CSBS) and the Evaluation and Nurturing Relationship Issues, Communication and Happiness (ENRICH). Data were analyzed using SPSS19.0 and Amos26.0. Results of t-test and analysis of correlation, regression and structural equation model showed that the scores of marital commitment and marital quality of soldiers were significantly higher than that of their spouses. Compared to their spouses, soldiers reported higher frequency of having sacrifice behaviors and perceiving sacrifice behaviors of spouse. Furthermore, the marital commitment of military couples had significant influence on their own marital quality and frequency of perceiving each other's sacrifice behavior, while the commitment to spouse had a significant predictive effect on the marital quality of soldiers and their spouses. Military couples' perception of the frequency of each other's sacrifice behavior partially mediated the effect of marital commitment on their marital quality. Soldiers' perception of spouse’s sacrifice behavior frequency significantly predicted the marital quality of their spouses, however, their spouses' perception of soldiers' sacrifice behavior frequency did not significantly predict the marital quality of soldiers.